Ectopic expression of GDF15 in cancer-associated fibroblasts enhances melanoma immunosuppression via the GFRAL/RET cascade - Zhiheng Lin; Li Lin; Yisheng Chen; Yantao Ding; Xiaojing Wang; Zhiwen Luo; Zhenzhen Zhao; Zhijie Zhao; Huabao Cai; Wenyang Nie; Fu Zhao (Journal for ImmunoTherapy of Cancer)
Background A key aspect of tumor biology is the involvement of cancer-associated fibroblasts (CAFs) in shaping the immunosuppressive microenvironment. However, the dynamic and complex key roles of CAFs in the melanoma immune microenvironment have not been elucidated.Methods The CAFs landscape in melanoma was characterized using single-cell RNA-seq and spatial transcriptomics. Molecular dynamics simulations were employed to validate the interactions between CAFs and melanoma cells. Bulk RNA-seq was used to establish a prognostic model. To validate the expression of key targets, western blotting, quantitative real-time PCR, and ELISA were performed. The molecular interactions were confirmed via co-immunoprecipitation, chromatin immunoprecipitation, and luciferase gene reporter assays. In-depth molecular mechanisms were explored using lentiviral transfection, cell co-culture experiments, recombinant protein rescue experiments, flow cytometry, knockout mice, and Cre-loxP system mice.Results This study identified a unique group of CAFs expressing high levels of growth differentiation factor 15 (GDF15). The paracrine secretion of GDF15 was regulated by the transcription factor FOXP1, which subsequently binds to the TGFBR2 receptor on melanoma cells, driving their proliferation and metastatic capacity. In addition, CAFs-derived GDF15 interacts with the GFRAL receptor on melanoma cells, thereby promoting RET phosphorylation and triggering downstream signaling axes, inducing increased tumor cell stemness and secretion of inflammatory factors CCL18 and TGF-β. This cascade reaction ultimately induces macrophage polarization to the immunosuppressive M2 phenotype, assists in the establishment of an immunosuppressive microenvironment, and leads to accelerated melanoma lung metastasis.Conclusion By integrating single-cell RNA-seq, spatial transcriptomics, bulk RNA-seq, molecular dynamics simulation and complete experimental design, this study comprehensively characterized that ectopic expression of CAFs-derived GDF15 can act as an accomplice in melanoma progression by inducing increased tumor cell stemness and macrophage M2 polarization, reshaping the immune landscape of melanoma, and providing new ideas and new targets for precision immunotherapy of melanoma.